The importance of library Akademi Pengajian Islam Universiti Malaya (Apium), Nilam Puri, Kota Bharu Kelantan in contributing knowledge to the community / Mohd Raif Masaud - Masaud, Mohd Raif (Universiti Teknologi MARA Cawangan Kelantan, 2013)
Library services are one of the services that are important in the field of education and intellectual development of society. As an innovation center, libraries play an important role in creating a society of culture and love reading knowledge. In line with the government's intention to make Malaysia a regional education hub, then evaluation of library services should be focused. This study was conducted to determine the importance of the Library Academy of Islamic Studies University of Malaya Nilam Puri in contributing knowledge to the community. The factors involved in the study are services, staff, services, Islamic References book, material, good environment and activities. A total of 106 respondents is randomly selected which are community or users of this library. This study collected the data through questionnaires which are directly distributed to the users. The data were analyzed using Logistic regression. The overall findings of the study showed that the visitors are satisfied with the staff at the counter have a friendly attitude, the various types of magazines and newspapers is limited, the new edition of the book should be added to the other general and the library enables me to accomplish tasks faster. It is found that others factors should be improved. At the end of the study, the researcher had proposed several suggestions to the related parties to ensure full attention was paid towards the studied problems